2014
DOI: 10.1016/j.bbmt.2013.11.025
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Symptoms Measured by the National Institutes of Health Lung Score Predict Overall Survival, Nonrelapse Mortality, and Patient-Reported Outcomes In Chronic Graft-Versus-Host Disease

Abstract: The 2005 NIH Consensus Conference recommended assessment of lung function in patients with chronic graft-versus-host disease (GVHD) by both pulmonary function tests (PFTs) and assessment of pulmonary symptoms. We tested whether pulmonary measures were associated with non-relapse mortality (NRM), overall survival (OS) and patient reported outcomes (PRO). Clinician and patient-reported data were collected serially in a prospective, multicenter observational study. Available PFT data were abstracted. Cox regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
66
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 81 publications
(66 citation statements)
references
References 34 publications
0
66
0
Order By: Relevance
“…[1][2][3] Lung cGVHD or bronchiolitis obliterans syndrome (BOS) results from immune attack of the small airways, leading to fibrotic occlusion and subsequent obliteration. BOS is often an asymptomatic, insidious disease occurring within the first 2 years of HCT with other manifestations of cGVHD.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Lung cGVHD or bronchiolitis obliterans syndrome (BOS) results from immune attack of the small airways, leading to fibrotic occlusion and subsequent obliteration. BOS is often an asymptomatic, insidious disease occurring within the first 2 years of HCT with other manifestations of cGVHD.…”
Section: Introductionmentioning
confidence: 99%
“…In analysis of individual organ systems, this scoring system has been predictive of meaningful end points such as OS and NRM. [19][20][21][22][23][24] However, when imputed into a calculated composite response, measures have had variable correlation with clinician-reported response and survival outcomes. Although 1 study demonstrated good correlation between response calculated per the 2005 NIH consensus criteria and clinician-reported response, and a survival advantage to those patients who had a favorable response (partial response [PR] or better) at 6 months, this study had a small number of patients evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, a symptombased lung score predicted overall survival and nonrelapse mortality in stem cell transplant recipients with chronic graft versus host disease (Palmer et al, 2014). Based on the prognostic signal seen to date in diverse cancer settings from infrequently collected HRQOL and symptom data, it is conceivable that PGHD streams of frequent, longitudinal symptom, HRQOL, functional status, and physical activity data may provide important prognostic and perhaps predictive information at multiple time points for patients on therapeutic clinical trials.…”
Section: Predicting and Understanding Therapeutic Outcomesmentioning
confidence: 99%